OWNERSHIP RETENTION, KOMISARIS INDEPENDEN, PROPRIETARY COST, DAN PENGUNGKAPAN INTELLECTUAL CAPITAL DALAM PROSPEKTUS IPO - Sari, Ririk Yunita Hendry Kusworo (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2012)
ABSTRACT The first aim of this paper is to look for the possible determinants of the intellectual capital disclosure policy of Indonesian IPOs by relating the content of their prospectuses to ownership retention and independent commissioner. The second aim of this paper is to examine the truth that proprietary cost affects relationship between ownership retention and intellectual capital disclosure, in which proprietary cost was used as a moderating variable. The main result is that ownership retention play a major role in the intellectual capital disclosure policy of firms. Ownership retention has been found positively and significantly affected on intellectual capital disclosure. Inversely, no significant effect was found for independent commissioner. Finally, the result also showed no significant effect of proprietary cost moderating variable on relation between ownership retention and intellectual capital disclosure, leading to H3 rejection. Keywords: intellectual capital disclosure, ownership retention, independent commissioner, proprietary cost, prospectus.